Outcome of nurses’ training on treatment of selected diseases, utilising integrated management of childhood illness module inagege local governemnt, Lagos State - Omolayo, Fadipe Ololade (International Journal of Research in Medical Sciences, 2020)
Background: In developing countries, parents seek health care for their sick children daily at available health centers, pharmacies, hospitals and traditional healing centers, but the care received are not always adequate, this invariably result in use of obsolete ideas and regimens in the care of sick children. However, it was observed that some nurses do not treat sick children according to IMCI module hence the objective of the study is to explore the outcome of nurses training in the treatment of selected childhood diseases utilizing IMCI. Methods: The study utilized one group pre-posttest quasi experimental research design. Total enumeration was used to enroll 150 participants. Two research instruments were used to collect data with reliability index of 0.803 and 0.617. Inferential statistics was used to test the hypotheses at 0.05 level of significance. Data were collected over six weeks in three phases. Results: Results revealed significant differences between pre and post intervention mean scores of nurses knowledge in the treatment of malaria (t=22.626, p=0.00); pneumonia (t=19.760, p=0.00); and diarrhoea (t=19.608, p=0.00). Conclusions: The training package used in this study enhanced the knowledge in the treatment of selected childhood illness. It is therefore recommended that there is need to train all nurses working at the primary health centers on the use of integrated management of childhood illness module which will contribute to the reduction of infant morbidity and mortality rate in Ages local government area of Lagos State.